Mid-Term Outcome of Total Hip Arthroplasty Using a Short Stem. (December 2016) - Malhotra, Rajesh; Kumar, Vijay
Purpose: To review the outcome of total hip arthroplasty (THA) using a short femoral stem in 33 hips. Methods: Records of 33 hips in 20 men and 10 women aged 25 to 40 (mean, 30) years who underwent cementless THA using a short femoral stem by a single senior surgeon were reviewed. The diagnosis included avascular necrosis (n=9), ankylosing spondylitis (n=12), rheumatoid arthritis (n=7), post-traumatic arthritis (n=4), and Hurler syndrome (n=1). Clinical outcome was assessed using the Harris Hip Score. Radiological outcome was assessed according to a modified Gruen zoning system. Stem positioning (neutral, varus, valgus) and bone contact were evaluated, as were fixation and early host response as well as subsidence and changes in the calcar region (zone 5). Trabecular response (trabecular attachment), spot welds, cortical hypertrophy, and pedestal formation were determined. Heterotopic ossification was graded by the Brooker classification. Results: The mean follow-up period was 6.5 years. The mean Harris Hip Score improved from 40 to 90. All hips achieved immediate postoperative stability. No patient had thigh pain. Four hips had varus placement (5°–7°) of the stem; all were asymptomatic and remained stable without any migration. Evidence of proximal load transfer (endosteal spot welds) between the endosteum and the stem in zones 2 and/or 4 was noted in 12 hips on both sides and in 8 hips on the lateral side only. At one year, all stems showed evidence of osseointegration. None had subsidence or progressive varus migration. There was no radiolucent line or osteolysis around the stem, pedestal formation or buttressing at the prosthesis tip, or cortical hypertrophy. One patient had grade I heterotopic ossification that was not clinically significant. One patient had a 1.5 cm leg lengthening. One patient had a discharging sinus, a loosened acetabular component, and intrapelvic migration at 2 years and underwent implant removal and debridement. One patient developed a crack in the proximal femur even with the smallest stem. The stem was fixed with cerclage wiring and remained stable with no migration. Conclusion: A short femoral stem design that transfers load proximally through a prominent lateral flare achieved good short-term outcome in younger patients. Nonetheless, the ease of removal and preservation of bone at the time of revision should guide the choice of the design of the short stem.